Studi Pemetaan Sistematis Karir Perumahan Studi Kasus: Kota Yogyakarta - Yulinda Rosa (Jurnal Permukiman, 2024)
The highest proportion of family spending. Efficiency in the provision of housing needs to be done through the provision of the right place to live, at the right time, and with the right people, so that there are no vacancies in the house, one of which is through the application of the Housing Career concept. The housing backlog is currently increasing, and although several housing subsidy programs have been implemented, one of the problems is the mismatch between dynamic housing demand and the current static housing supply. The purpose of this article is to identify, classify, and perform thematic analysis of the current literature to create an understanding of residential careers. The systematic mapping study (SMS) method is used to review research that has been published from time to time. By using this method the fokus, locus, type of research, relying on the Scopus electronic database mapping. Furthermore, an overview of housing careers in Indonesia is given based on city-scale sampling data.